INTEREST RATE PASS-THROUGH IN LITHUANIA - Vytenis Lapinskas (Ekonomika, 2011)
The paper considers the pass-through of the interbank and retail interest rates for the case of Lithuania. The need for the interest rate transmission analysis has grown during the volatile market period caused by the global financial crisis. The objective of the article is to check theoretical and statistical aspects of domestic currency (litas) interest rate pass-through from interbank to retail interest rates and, specifically, to determine whether the recent global financial crisis has affected this process. Methods used in the article include a systemic analysis of related studies, historical data analysis and statistical testing. The analysis is expanded to cover the alternative interest rate-related variables in order to check the consistency of the pass-through of the litas interest rate over the period from October 2004 to December 2010. Results of the research show that though the lending interest rates have increased and the interest rate relationship has transformed over this period, there is no proof that changes in the bank interest rate setting policy has led to abnormal profits for banks.